BIOACTIVE SECONDARY METABOLITES DERIVED FROM ENDOPHYTES: A REVIEW - SHOBHA SINGARAPALLE; M. ABDULLAH HARH; CHEEPURI GOWTHAM PHANINDRA; D. JAGADEESWARA REDDY; PATRICK FRANCIS KIMARIYO; MURALI KRISHNA KUMAR MUTHYALA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Endophytes comprise diverse bacteria, fungi, and actinomycetes that reside harmlessly within plant tissues, fostering complex ecological interactions that significantly enhance plant growth, stress resilience, and disease resistance. Since their discovery in the early 19th century, endophytes have become essential for sustainable agriculture, environmental conservation, and advances in therapy. They generate bioactive secondary metabolites such as paclitaxel (Taxol), camptothecin, podophyllotoxin, and vincristine, critically important in cancer treatment. The varied biosynthetic pathways for metabolites like terpenoids, polyketides, alkaloids, flavonoids, and phenylpropanoids emphasize the biochemical versatility of endophytes. Leveraging these bacteria biotechnologically offers a sustainable and scalable alternative to conventional plant-based extraction, addressing the growing global demand for medicinal compounds while minimizing ecological impact. This review presents a detailed analysis of endophytes' classification, ecological roles, and industrial applications, highlighting their significant contributions to advanced pharmaceutical research, sustainable agriculture, and bioremediation. Expanding research on plant-endophyte relationships may result in discovering new bioactive compounds, advancing the convergence of microbiology, biotechnology, and environmental science.